Identification of preoperative factors and postoperative outcomes in relation to delays in surgery for hip fractures. Issue 4 (2022) - Fluck, Ben; Yeong, Keefai; Lisk, Radcliffe; Robin, Jonathan; Fluck, David; Fry, Christopher H; Han, Thang S
No abstract available